Production and Application of Organic Fertilizer for White Leg Shrimp and Milkfish Cultivation - Indriyani Nur; Yusnaini Yusnaini; Baheri Baheri (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2021)
The slow growth of white leg shrimp and milkfish cultivation became a concern in the location of community service activity (PKM). This was mainly due to food limitation, especially concerning the difficulty in natural food development. The purpose of this endeavor is to apply the production technology and application of organic fertilizer for the cultivation of white leg shrimp and milkfish along the marginal embankments. This endeavor was carried out in April to November 2019 in Mondoe Village, Konawe Selatan District, Southeast Sulawesi. This activity was manifested by providing production facilities, training, production of organic fertilizer, the use of organic fertilizer, white leg shrimp and milkfish cultivation, monitoring, and activities evaluation. The implementation of this activity was able to increase the knowledge, perception, and skills of participants as partners in producing fermented organic fertilizer. The application of the use of organic fertilizer was able to provide alternatives and overcome the limitation of fertilizer for aquaculture businesses in embankments. The results of this PKM were proven to be able to improve partners' knowledge and skills and provide solutions in overcoming the limitation of fertilizer especially in terms of aquaculture businesses in embankments.